The Institutional Architecture of the Eurozone and the Dynamics of EU Transformations - Surdej , Aleksander (Studia Oeconomica Posnaniensia, 2018)
The article attempts to show the functioning and the challenges to the stability of the Eurozone in the light of a hypothesis linking monetary systems with the political system of a unitary state. The theoretical reasons and historical circumstances behind the introduction of the euro are discussed the economic results of its first 10 years of the existence and differentiated consequences of the global financial crisis to the countries of the Eurozone are shown. Next, proposals for the reforms of the institutional architecture of the Eurozone which are supposed to improve its stability and efficiency are examined. In conclusion, the paradoxical properties of the political instrumentality of having a single currency as a means to increase solidarity and prosperity of European nations are pointed out.